Biomechanical Comparison of the New-Generation Implant Designed for the Fixation of Patella Fractures with the Tension Band Method - Ahmet Ülker; Ahmet Burak Satılmış; Zafer Uzunay; Tolgahan Cengiz; Abdurrahim Temiz; Mustafa Yaşar; Tansel Mutlu; Uygar Daşar (Medicina, 2025)
Background and Objectives: This study compares the biomechanical performance of a new-generation implant designed for patella fracture fixation with the traditional tension band method. Its goal is to assess fracture fixation’s stability and the new implant’s potential advantages in reducing complications such as skin irritation, pain, and implant failure. Materials and Methods: In this experimental study, 20 calf patellae were divided into two groups. The first group was treated with the traditional tension band method, while the second group received the new-generation implant, designed using finite element analysis (FEA) for optimization. Both groups underwent biomechanical testing with axial forces at a 45° flexion angle to simulate real-life load conditions. The maximum forces at which mechanical insufficiency occurred were recorded. Data were analyzed using SPSS for statistical comparison. Results: Finite element analysis revealed that the new-generation implant provided better fracture line stability than the tension band method under applied forces. In the biomechanical tests, the maximum force at which mechanical insufficiency occurred was significantly higher in the new-generation implant group (1130 ± 222 N) compared to the tension band method group (680.5 ± 185.4 N), with a statistically significant difference (p = 0.008). The new implant demonstrated superior fixation, with better resistance to distraction forces. Conclusions: The new-generation implant offers enhanced biomechanical stability compared to the traditional tension band method, particularly regarding fixation strength under applied forces. This study supports the potential of the new implant to improve fixation stability and reduce common complications associated with patella fracture surgeries. Further testing in more extensive human cadaver studies is recommended to confirm these findings and assess long-term clinical outcomes.